Galvanic Vestibular Stimulation Produces Cross-Modal Improvements in Visual Thresholds - Voros, Jamie L.; Sherman, Sage O.; Rise, Rachel; Kryuchkov, Alexander; Stine, Ponder; Anderson, Allison P.; Clark, Torin K. (Frontiers in Neuroscience, 2021)
Background: Stochastic resonance (SR) refers to a faint signal being enhanced with the addition of white noise. Previous studies have found that vestibular perceptual thresholds are lowered with noisy galvanic vestibular stimulation (i.e., “in-channel” SR). Auditory white noise has been shown to improve tactile and visual thresholds, suggesting “cross-modal” SR. Objective: We investigated galvanic vestibular white noise (nGVS) (n=9 subjects) to determine the cross-modal effects on visual and auditory thresholds. Methods: We measured auditory and visual perceptual thresholds of human subjects across a swath of different nGVS levels in order to determine if some individual-subject determined best nGVS level elicited a reduction in thresholds as compared the no noise condition (sham). Results: We found improvement in visual thresholds (by an average of 18%, p = 0.014). Subjects with higher (worse) visual thresholds with no stimulation (sham) improved more than those with lower thresholds (p = 0.04). Auditory thresholds were unchanged by vestibular stimulation. Conclusions: These results are the first demonstration of cross-modal improvement with galvanic vestibular stimulation, indicating galvanic vestibular white noise can produce cross-modal improvements in some sensory channels, but not all.